Peningkatan Awareness Skena Musik Independen Indonesia (Studi Konvergensi Media dan Do It Yourself) - Rizky Ramandhika Putra; Irwansyah Irwansyah (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this research is to raise awareness of the Indonesian indendent music scene with a music collective called Subnoise based in Bekasi, West Java. The type of research that will be used is qualitative research using data analysis techniques in the form of in-depth interviews in a number of analysis units, namely individuals who are actively involved in the collective independent scene called Subnoise. The data source used is the writings on the website about what Truth is and the history of its formation. In addition, the author will also listen to and watch interviews or interviews conducted by podcasters, radio, and also a Youtube channel that appoints Subnoise as their source and takes the essence of the event. This study concludes that with the emergence of music collectives in the independent scene, one way for organizations and independent music lovers to build a cultural network that binds each other, both in terms of musicians, their work, and their fans, and can also differentiate them from the scene. mainstream or mainstream. The common thoughts and tastes of the members became the starting point for its establishment. Subnoise uses awareness raising methods such as posts on social media Twitter, Instagram, and channels on Youtube to promote awareness of the independent scene they serve.